How Elastic is the Labour Supply of Female Migrants Relative to the Labour Supply of Female Natives? - Tanja Fendel (De Economist, 2020)
This study estimates the wage elasticities of migrants and natives by using data from the German Socio-Economic Panel from 1984 to 2015 and a grouping instrumental variable estimator. Female migrants who live with a partner have lower own- and cross-wage elasticities than respective female natives, and the elasticities of non-Western female migrants are insignificant. The relationship between participation and elasticity is not in all cases positive, but parallel to labour market integration, the time since migration increases the elasticities of women. Elasticities indicate the potential to increase participation; therefore, it is especially important for non-Western female migrants to remove barriers to flexible wage responses.
Keywords: F22; J22; 330; Labour supply behaviour of women; Migration; Grouping estimator